Pergeseran Otoritas Hukum Islam Perspektif Fenomenologi - Muhaimin, Muhaimin (Madania: Jurnal Kajian Keislaman, 2018)
Abstract: The Shift of Islamic Law Authority of Phenomenological Perspective. This article seeks to explain the new phenomenon of religious authority in Indonesia, especially in terms of Islamic law and discourse, which seems more authoritative because it is more interactive and direct to the audience (who asks), and is connected through social media; as did Nasaruddin Umar, Musthofa Bisri, Nadhirsyah Hossen, Khalid Basallamah, Abdus Shomad and others. They have different approaches from organizational habits; where Nahdatul Ulama‘, Muhammadiyah, and other organizations, still use the classical approach in the formulation of Islamic law and the study of the problems of society. Not only that, there is also a difference in the delivery model of an organizational-based authority model in the dissemination of its fatwa. Based on this component also, the author makes the phenomenology of religion (assessment based on the structure of human consciousness) as a study approach and methodical to see the phenomenon. At the same time provide a picture of what should be realized in the context of building Islamic law in accordance with Islamic values   and keindonesian. As is known, the personal outlook that ‘seems to’ break away from institutional influences becomes highly subjective, and based on their own comprehension ability.